Knowledge Sharing Terhadap Kinerja Bisnis Pada Perusahaan BUMN - Masrokhah, Siti; Afif Hendri Putranto (Awatara Publisher, 2024)
In the current era of disruption, organizations are dynamic entities in an ever-changing world that strive to fulfill their missions through short-medium and long-term programs and goals. In the midst of the Covid-19 Pandemic PT. Angkasa Pura II Kualanamu International Airport is facing various situations that have an impact on company operations. In dealing with the Covid-19 situation, various work adaptations are needed to be able to keep the company running. Knowledge management is needed in this condition to support business performance, where the important point in knowledge management is knowledge sharing. This research aims to analyze how knowledge sharing influences business performance at PT. Angkasa Pura II Kualanamu International Airport. As well as describing how knowledge sharing and business performance at PT. Angaksa Pura II Kualanamu International Airport. This research uses quantitative research with an associative approach. Sampling used 84 respondents as research samples. Primary data in this research was obtained from distributing questionnaires via Google Form and secondary data was obtained through literature study. The analytical methods used are validity testing, classical assumption testing, reliability testing, simple linear regression analysis and hypothesis testing. The results of the research conducted show that the knowledge sharing variable (X) has a positive and significant effect on Business Performance. Based on the coefficient of determination test, there is a fairly close relationship between knowledge sharing and Business Performance with an R value of 0.332. Through the adjusted R square value, there is a contribution of knowledge sharing of 32.4% to Business Performance. Meanwhile, the remaining 67.6% was influenced by other variables not explained in this study.